2016
DOI: 10.18410/jebmh/2016/1134
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Macular Thickness After Phacoemulsification vs. Manual Sics by Ocular Coherence Tomography in Diabetic Patients

Abstract: BACKGROUND The aim of the study is to evaluate the change in macular thickness by optical coherence tomography after uncomplicated phacoemulsification versus uncomplicated manual SICS in known diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Analysis of PHACO and SICS procedure on senile cataract showed that the macular thickness was higher in SICS group. 24 The authors showed significant difference in macular thickness between PHACO and SICS group on 3rd day, 7th day, 3rd month and 6 months follow up. 24 The results of our study were similar to that analysis, though their study was on senile cataract and ours was on adolescent patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Analysis of PHACO and SICS procedure on senile cataract showed that the macular thickness was higher in SICS group. 24 The authors showed significant difference in macular thickness between PHACO and SICS group on 3rd day, 7th day, 3rd month and 6 months follow up. 24 The results of our study were similar to that analysis, though their study was on senile cataract and ours was on adolescent patients.…”
Section: Discussionmentioning
confidence: 86%
“…24 The authors showed significant difference in macular thickness between PHACO and SICS group on 3rd day, 7th day, 3rd month and 6 months follow up. 24 The results of our study were similar to that analysis, though their study was on senile cataract and ours was on adolescent patients. We found significant difference in macular thickness between the two groups from 1st postoperative day to 168th postoperative day, the highest difference being on the 42nd postoperative day.…”
Section: Discussionmentioning
confidence: 86%
“…Many authors showed significant difference in macular thickness between PHACO and SICS group on 3 rd day, 7 th day, 3 rd month and 6 months post-operative follow ups. 9 A study done by Dr. Indranil Roy et al on total 224 patients who were randomised to two groups-phaco and SICS, found mean central foveal thickness in SICS group was more than that of phaco group on post-op 1 st , 7 th , 42 nd and 180 th day. On day 180, mean central foveal thickness in SICS group was significantly (p=0.032) more than phaco group.…”
Section: Discussionmentioning
confidence: 99%
“…Modern cataract surgery with a small and self-sealed corneal incision along with the use of a foldable intraocular lens in the bag reduces CME. Ocular Coherence Tomography is used to detect macular edema is a newer real-time investigation 5 . There is little data available to compare between two groups, small incision cataract surgery (SICS) and Phacoemulsification (PHACO) in a patient with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%